2015
DOI: 10.1007/s10071-015-0880-2
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons (Columba livia) fail to connect dots in learning biological motion

Abstract: Biological motion point-light displays provide a powerful method for studying motion perception. Nonhuman animals are capable of discriminating point-light displays, but it remains unknown how they perceive biological motion in these displays. We trained two groups of pigeons to discriminate video stimuli using two different classification rules. The motion-congruent group was trained to discriminate full-detail and corresponding point-light displays of pigeons from full-detail and point-light displays of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Previous reports argued that rodents discriminate BM displays from other stimuli; however, it is not known whether the animals perceived moving dots in an integrated way to perform tasks (MacKinnon et al, 2010 ; Foley et al, 2012 ). Non-human species often fail to group each motion of dots as a single stimulus (Dittrich et al, 1998 ; Yamamoto et al, 2015 ). Consequently, how local features contribute to the performance of the animal should be examined with care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports argued that rodents discriminate BM displays from other stimuli; however, it is not known whether the animals perceived moving dots in an integrated way to perform tasks (MacKinnon et al, 2010 ; Foley et al, 2012 ). Non-human species often fail to group each motion of dots as a single stimulus (Dittrich et al, 1998 ; Yamamoto et al, 2015 ). Consequently, how local features contribute to the performance of the animal should be examined with care.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, have distinguished between the ability to discriminate stimuli acquired through simple training and other discriminative responses (Pavlova, 2012 ). Some species cannot generalize their learning to novel BM displays (baboons; Parron et al, 2007 ; rats: MacKinnon et al, 2010 ; pigeons: Dittrich et al, 1998 ; Yamamoto et al, 2015 ; rhesus macaques: Vangeneugden et al, 2010 ). The discrimination training employed in these studies might induce a behavioral strategy in which the animals use local movements of dots as a discriminative cue.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Blake (1993) successfully trained cats to differentiate between PLFs depicting cats in motion versus PLFs depicting an inverted or scrambled version of the same stimuli. Other non‐human animals tested with conspecific‐shaped PLFs using discrimination tasks, including visual search tasks, include pigeons (Dittrich, Lea, Barrett, & Gurr, 1998; Qadri, Asen, & Cook, 2014; Troje & Aust, 2013; Watanabe & Troje, 2006; Yamamoto, Goto, & Watanabe, 2015), chimpanzees (Tomonaga, 2001), baboons (Parron, Deruelle, & Fagot, 2007) and rats (MacKinnon, Troje, & Dringenberg, 2010). Second, research has also used methods that study animals' spontaneous preference for certain types of PLFs, testing approaching behaviour in chicks (Regolin, Tommasi, & Vallortigara, 2000; Vallortigara, Regolin, & Marconato, 2005; Yamaguchi & Fujita, 1999) and quails (Yamaguchi & Fujita, 1999) and preferential looking in marmosets (Brown, Kaplan, Rogers, & Vallortigara, 2010) and in dogs (Eatherington, Marinelli, Lõoke, Battaglini, & Mongillo, 2019; Ishikawa, Mills, Willmott, Mullineaux, & Guo, 2018; Kovács et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, no such effect of scrambling but an effect of inversion was found on approaching preference in chicks (Vallortigara & Regolin, 2006). Second, some of the above studies concluded that animals were capable of detecting biological motion in PLFs (Brown et al, 2010; Dittrich et al, 1998; Ishikawa et al, 2018; Kovács et al, 2016; Regolin et al, 2000; Troje & Aust, 2013; Vallortigara et al, 2005; Watanabe & Troje, 2006; Yamaguchi & Fujita, 1999), whereas others reported negative results and stated that the positive findings of animals recognising biological motion in PLFs may be due to animals using certain configurational properties of the PLF, that is paying attention to sub‐configurations of the dots rather than perceiving the PLF stimulus as a whole representing conspecifics (Eatherington et al, 2019; Parron et al, 2007; Qadri et al, 2014; Tomonaga, 2001; Yamamoto et al, 2015). In particular, when animals gain food or are reinforced during repeated training occasions, they have the chance to learn about configurational properties of PLFs.…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus on avian species, because most of them have a well-developed but totally different visual system than that in the primate brain. Previous studies (mostly on pigeons) have demonstrated that avian species are sensitive to visual motion: they can distinguish various motion patterns such as the speed and direction of stripes 9,10 , global dot motion pattern, object motion, and biological motion 1117 . Physiological studies have found that visual motion is processed across the different visual processing stages in the pigeon brain (e.g.…”
Section: Introductionmentioning
confidence: 99%